Managerial rents and regulatory intervention in troubled banks - Noe, T; Rebello, M; Wall, L (1996)
In this paper we investigate the effects of regulatory policies on troubled banks. In our analysis banks' portfolio decisions are unobservable and are made by management. Management's decisions are influenced by the compensation and intervention policies of shareholders and regulators as well as the impact of its portfolio choice on its share of firm-specific rents. We demonstrate that firm-specific rents may induce managers to prefer risky asset portfolios. These incentives may be exacerbated by shareholder-designed compensation contracts intended to align managerial and stockholder interests. Depending on the parametric specifications of the model, both the often-criticized practice of regulatory forbearance and the compensation regulations proposed in the Federal Deposit Insurance Corporation Improvement Act of 1991 may form part of the deposit-insurance-loss-minimizing regulatory policy.